High‐fidelity, high‐isotropic‐resolution diffusion imaging through gSlider acquisition with B1+ and T1 corrections and integrated ΔB0/Rx shim array. Issue 1 (1st August 2019) - Liao, Congyu; Stockmann, Jason; Tian, Qiyuan; Bilgic, Berkin; Arango, Nicolas S.; Manhard, Mary Kate; Huang, Susie Y.; Grissom, William A.; Wald, Lawrence L.; Setsompop, Kawin
Abstract : Purpose: B 1 + and T 1 corrections and dynamic multicoil shimming approaches were proposed to improve the fidelity of high‐isotropic‐resolution generalized slice‐dithered enhanced resolution (gSlider) diffusion imaging. Methods: An extended reconstruction incorporating B 1 + inhomogeneity and T 1 recovery information was developed to mitigate slab‐boundary artifacts in short‐repetition time (TR) gSlider acquisitions. Slab‐by‐slab dynamic B 0 shimming using a multicoil integrated Δ B 0 / Rx shim array and high in‐plane acceleration ( R inplane = 4) achieved with virtual‐coil GRAPPA were also incorporated into a 1‐mm isotropic resolution gSlider acquisition/reconstruction framework to achieve a significant reduction in geometric distortion compared to single‐shot echo planar imaging (EPI). Results: The slab‐boundary artifacts were alleviated by the proposed B 1 + and T 1 corrections compared to the standard gSlider reconstruction pipeline for short‐TR acquisitions. Dynamic shimming provided >50% reduction in geometric distortion compared to conventional global second‐order shimming. One‐millimeter isotropic resolution diffusion data show that the typically problematic temporal and frontal lobes of the brain can be imaged with high geometric fidelity using dynamic shimming. Conclusions: The proposed B 1 + and T 1 corrections and local‐field control substantially improved the fidelity of high‐isotropic‐resolution diffusion imaging, with reduced slab‐boundary artifacts and geometric distortion compared to conventional gSlider acquisition and reconstruction. This enabled high‐fidelity whole‐brain 1‐mm isotropic diffusion imaging with 64 diffusion directions in 20 min using a 3T clinical scanner.